Evidence for the hb (1P) meson in the decay γ(3S) → π0hb(1P) - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Using a sample of 122×106 Υ(3S) events recorded with the BABAR detector at the PEP-II asymmetric-energy e+e− collider at SLAC, we search for the hb(1P) spin-singlet partner of the P-wave χbJ(1P) states in the sequential decay Υ(3S)→π0hb(1P), hb(1P)→γηb(1S). We observe an excess of events above background in the distribution of the recoil mass against the π0 at mass 9902±4(stat)±2(syst) MeV/c2. The width of the observed signal is consistent with experimental resolution, and its significance is 3.1σ, including systematic uncertainties. We obtain the value (4.3±1.1(stat)±0.9(syst))×10−4 for the product branching fraction B(Υ(3S)→π0hb)×B(hb→γηb).
Im Titel ist "b" tiefgestellt
Im Titel ist "0" hochgestellt
Gesehen am 12.08.2022